Organisational Commitment and Turnover Intentions: Does Self-Efficacy Matter? - Opolot, Julius Samuel; Lagat, Charles; Kipsang, Stanley (SEISENSE (PRIVATE) LIMITED, 2023)
Purpose- This paper examined the relationship between organisational commitment, self-efficacy, and turnover intentions among academic staff in universities in Uganda, a developing nation.Design/Methodology- This research was undertaken via a cross-sectional research design to test the hypotheses using quantitative data collected from 574 academic staff at selected universities in Uganda. Hayes’s PROCESS macro (Version 4.2) was used to carry out a moderation analysis. Findings- The results indicate that interaction between self-efficacy and organisational commitment enhanced turnover intention. Academic staff with high levels of commitment, are less likely to engage in turnover behaviour at high levels of self-efficacy. Practical Implications- Drawing on empirical evidence, university managers seeking to improve staff retention need to adopt strategies that boost self-efficacy in order to instantly support organisational commitment. Adoption of participative work culture, equity, training, teamwork, and inclusiveness is an important signal and source of social information that the university values its employees and their stay.